2017
DOI: 10.1002/jez.b.22751
|View full text |Cite
|
Sign up to set email alerts
|

Specification of Larval Axes of Partial Embryos in the Temnopleurid Temnopleurus toreumaticus and the Strongylocentroid Hemicentrotus pulcherrimus

Abstract: Many sea urchins, including the strongylocentroid Hemicentrotus pulcherrimus, produce an amniotic cavity on the left for adult rudiment formation at the late larval stage. In contrast, temnopleurids form a cell mass at the early larval stage instead of an amniotic cavity. Although the mechanisms establishing left-right polarity of the amniotic cavity involve cell-cell interactions and signaling pathways, corresponding pathways for the cell mass are unknown. We analyzed the effects of blastomere isolation on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Next, we analyzed the number of Mesos necessary for CM formation, by isolating the Mesos at the 16‐cell stage. It was reported that larvae of T. toreumaticus derived from each blastomere isolated at the 2‐ or 4‐cell stage exhibited the potential to form a CM (Kitazawa et al, 2017), and this result indicated that CM formation requires at least 2 Mesos. In the present study, CM formation was confirmed at approximately 4 days after fertilization.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Next, we analyzed the number of Mesos necessary for CM formation, by isolating the Mesos at the 16‐cell stage. It was reported that larvae of T. toreumaticus derived from each blastomere isolated at the 2‐ or 4‐cell stage exhibited the potential to form a CM (Kitazawa et al, 2017), and this result indicated that CM formation requires at least 2 Mesos. In the present study, CM formation was confirmed at approximately 4 days after fertilization.…”
Section: Resultsmentioning
confidence: 93%
“…The size of the CM in specimens derived from a single blastomere at the 2-cell stage increased from about 15 µm 4 days after fertilization to 25 µm 5 days after fertilization (Kitazawa et al, 2017). This suggests that at least 4 Mesos are needed for an embryo to form a CM with a normal size.…”
Section: Results Of the Blastomere Isolation Experiments Summarized Inmentioning
confidence: 97%
See 1 more Smart Citation
“…It is believed that among species of the infraorder Temnopleuridea (Camarodonta), patterning inputs for adult rudiment formation changed from the more external amniotic cavity to the internal CM, thereby providing greater protection for the rudiment (Kitazawa et al 2012(Kitazawa et al , 2014. Also, blastomere isolation during the two-and four-cell stages for T. toreumaticus caused atypical left-right polarity (Kitazawa, Nakano, Yamaguchi, Miyahara, & Yamanaka, 2017). However, the mechanisms of adult rudiment formation from the CM are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments with T. toreumaticus, it was reported that position of the CM was disturbed by treatments involving lower specific gravity and inhibition of H + /K + -ATPase activity (Kitazawa, Nakano, Kobayashi, & Yamanaka, 2013), with slightly different treatment effects than found with other species. Also, blastomere isolation during the two-and four-cell stages for T. toreumaticus caused atypical left-right polarity (Kitazawa, Nakano, Yamaguchi, Miyahara, & Yamanaka, 2017).…”
Section: Introductionmentioning
confidence: 99%